MANDALA AND MEANING: TYPOLOGY OF SYMBOLS AND STRATEGIES OF INTERPRETATION IN PATRICK WHITE’S NOVEL - Akhmedova, Shokhida (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2025)
This article presents atypological analysis of symbols in the novel The Solid Mandala by Patrick White, a major representative of Australian literature and a Nobel Prize laureate. The main aim of the study is to distinguish between the universal and contextual types of symbols used in the novel, to reveal their aesthetic, philosophical, and psychological dimensions, and to interpret them within the framework of various theoretical approaches. In addition, the article highlights the scholarly significance of applying complex interdisciplinary methods to the study of symbolism in Australian literature. As a methodological basis, several approaches are combined: N. Frye’s five phases of literary symbolism (literal, descriptive, formal, mythological, and anagogic) are applied to demonstrate the multilayered nature of symbols; C. Jung‘s archetypal psychology is used to analyze the mandala, quaternity, twin archetype, and individuation process; Y. Lotman’s structural-semiotic model serves to explain oppositions, boundaries, intertextual relations, and the interpretation of the house as a spiritual space; finally, P. Ricoeur’s hermeneutical conception is employed to consider the dual interpretation of symbols within the “hermeneutics of suspicion” and the “hermeneutics of faith.” The results show that the key symbols of The Solid Mandala—the mandala, the circle, the twin brothers (Arthur and Waldo), the house, Terminus Road, manuscripts, books, and dance episodes — function simultaneously on personal and archetypal as well as contextual and universal levels. For Arthur, the marbles symbolise spiritual wholeness and compassion, while Waldo‘s manuscripts and books signify his striving for intellectual perfection but ultimately represent spiritual emptiness. The central theme of the novel — the movement from duality to unity — is embodied through the oppositions of reason – emotion, speech – silence, and external order – inner meaning. The novelty of the article lies in the fact that Patrick White’s symbols are analyzed typologically within several theoretical frameworks simultaneously, thereby demonstrating the importance of symbolism in Australian literature. Moreover, this approach may serve as a methodological model for deeper exploration of symbols in other national literatures.
Keywords: Patrick White; symbolism; typology; mandala; twins; duality; archetype; individuation; Australian literature